Performance-Based Funding: A Panacea for Quality Assurance in Nigeria Higher Education - Atolagbe, Adedapo A.; Awodjii, Omotayo Adewale; Oluwalola, Felicia Kikelomo (International Journal of Educational Management, 2022)
The sad reality of the quality of graduates from Nigerian higher institutions has fell short of employers’ expectations. This has led these graduates been subjected to examinations before they are absorbed into their system and taken as graduate trainee. Poor funding has been identified as one of the causes of poor quality graduates of Nigerian higher institution. This among others informed this paper on how performance-based funding approach could serve as a measure of quality assurance in Nigerian higher education system. Literature was reviewed on the concept of Performance Based Funding (PBF) and quality assurance. Suggestions were made on how PBF can serve as catalyst to quality assurance in Nigerian higher education system. It was suggested that funding formulas should be linked to outputs such as increasing the number of students who attains credits and degree completion milestones in Nigerian higher education institutions.